Analysis of creative thinking skills on the Pythagorean theorem material in terms of self-confidence - Alyani, Fitri; Mercury Aminanti, Narin Ledy (Jurnal Pengembangan Pembelajaran Matematika (JPPM), 2022)
The purpose of this study is to describe the ability of students' creative thinking processes on the Pythagorean theorem material which is reviewed based on self-confidence. The subjects of this study were Junior High School students at grade VIII in Jakarta, as many as 120 students. This study uses a qualitative method with a descriptive approach. The stages carried out are: filling out a self-confidence questionnaire, testing creative thinking skills with Pythagoras theorem questions, interviews, analyzing data, drawing conclusions. Based on the results obtained, the high self-confidence classification of students affects the students' high mathematical creative thinking skills as well. Classification of self-confidence is moderate, then the students' mathematical creative thinking ability is quite good. Conversely, if the classification of a student's self-confidence is low, then a student’s mathematical creative thinking skills is also low. Keywords: Creative Thingking Skill, Pythagorean Theorem, Self-Confidence